2017
DOI: 10.1002/hed.24896
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of the human posterior cricoarytenoid muscle by the external branch of the superior laryngeal nerve

Abstract: The external branch of the SLN contributes to the ipsilateral posterior cricoarytenoid muscle innervation in one-third of the cases. This contribution is usually unilateral, but is occasionally bilateral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…To avoid bias, we excluded all studies that had an N equal to one [ 61 ] and studies reporting a prevalence of 100% [ 54 , 62 , 63 ] because the sample was chosen intentionally or for convenience and therefore gave this result. Fifteen studies met the criteria to be meta-analyzed based on the prevalence variable.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid bias, we excluded all studies that had an N equal to one [ 61 ] and studies reporting a prevalence of 100% [ 54 , 62 , 63 ] because the sample was chosen intentionally or for convenience and therefore gave this result. Fifteen studies met the criteria to be meta-analyzed based on the prevalence variable.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of vocal fold paralysis, CT muscle involvement may represent a high‐level injury above the bifurcation of the RLN and SLN or dual injuries involving the RLN and the external branch of the SLN. Branches between these nerves, known as Galen's anastomosis, have been reported to form a communicating nerve in human subjects . A human larynx dissection study performed by Maranillo et al showed the existence of communication branches between the RLN and SLN in 85% of cases, and half of these gave off collateral branches to the TA‐LCA muscle complex.…”
Section: Discussionmentioning
confidence: 99%
“…[ 35 - 39 ] The EBSLN also contributes to the ipsilateral innervation of the posterior cricoarytenoid muscle which is the main abductor muscle of vocal cord, in 1/3 of all cases, in addition to its contribution to the adductor function of the vocal cord. [ 40 ]…”
Section: Evidences Related With Motor Innervation Of the Larynxmentioning
confidence: 99%